Anaplastic lymphoma kinase (ALK)-rearranged pulmonary pleomorphic carcinoma successfully treated with crizotinib. Issue 8 (August 2018) - Lin, Liping; Huang, Fuxi; Chen, Fang; He, Yan; Hu, Jiazhu; Cao, Xiaolong
Pulmonary pleomorphic carcinoma (PPC) is rare, and the response of patients to conventional chemotherapy is very poor. Here we present a patient with anaplastic lymphoma kinase (ALK)-rearranged advanced PPC treated with crizotinib. Computed tomography revealed a mass in the left upper lung of a nonsmoking 60-year-old woman. Pathological findings using resected tissue were consistent with PPC stage 1A, T1bN0M0. Although the patient received adjuvant radiotherapy, the disease relapsed, quickly progressed, and remained PPC according to analysis of biopsied tissue. Although negative for epidermal growth factor receptor mutations, ALK rearrangements were detected in adenocarcinoma and spindle-cell components. The patient received crizotinib therapy and achieved a partial response for 7 months. This case indicates that patients with PPC, particularly those with adenocarcinoma, may harbor an epithelial component with the ALK rearrangement. Although the progression-free survival of patients treated with crizotinib is limited, they may obtain more benefit compared with conventional chemotherapy.